Servo Driven Hydraulic Cylinder Hydrostatic Guide Sleeve Temperature Field Analysis - SHAO Junpeng; XU Longfei; SUN Guitao (Journal of Harbin University of Science and Technology)
Hydraulic quadruped robot has the characteristics of running smoothly, loading strongly and adapting to the diversified environment, so the research of universities and enterprises is more extensive As the main driving element of quadruped robot, electrohydraulic servo driving cylinder has the characteristics of strong antibias load, stable highspeed movement and low friction In this paper, the temperature field of oil film in hydrostatic support guide sleeve is analyzed under eccentric load of electrohydraulic servo driving cylinder The state of oil film eccentric load is established by threedimensional modeling software The oil film is meshed by ICEM CFD software The oil film is simulated by FLUENT software and the hydraulic cylinder is subjected to the same eccentric load In this case, the variation of oil film temperature field of piston rod at different speeds is analyzed, and the region where the greatest oil film temperature occurs is determined